THE IMPACT OF WEATHER ON TRADING IN THE IRAQ STOCK EXCHANGE (World Economics and Finance Bulletin, 2025)
Due to the irregularity of the weather conditions in Iraq as a financially developing country, the research aimed to show what is the impact generated by fluctuating weather conditions on the one hand and severe weather conditions on the other hand on the trading condition in the Iraq Stock Exchange. Since the investor inside Iraq complains as a result of the weather conditions being very cold or very hot. The research dealt with two weather conditions when it rains and is accompanied by severe cold and when temperatures rise in the summer. The results showed that both phenomena affect trading in the Iraq Stock Exchange. The research put forward a set of recommendations, the most important of which was that investors should not be affected by weather conditions because an investment opportunity may be lost as a result of not going to the financial market due to the high cold or heat. Here, the investor needs awareness in order to get rid of the effects of being affected by the weather and not making the appropriate investment decision.